Pension system reforms, the capital market and saving - Andras Uthoff B. (CEPAL Review, 1997)
Pension system reforms seek to combine and reconcile both economic and social functions. On the basis of both conceptual aspects and the actual experience of Chile, this article illustrates the difficulties encountered in trying to make reforms fulfill both types of functions. These difficulties stem from two factors: i) the need to consider the reform of the pension system as a whole, where, parallel with the capitalization component, it is necessary to develop another unfunded component to finance the costs of the transition from one pension system to another, minimum pensions, and social welfare pensions; and ii) the need to distinguish between financial saving and real saving (or national saving in the national accounts sense) and to study the financial sector’s capacity to intermediate financial saving towards real investment. The Chilean experience confirms this view.